2022
DOI: 10.1021/acs.jmedchem.1c01211
|View full text |Cite
|
Sign up to set email alerts
|

Development of Radiohalogenated Osimertinib Derivatives as Imaging Probes for Companion Diagnostics of Osimertinib

Abstract: Osimertinib is an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor approved for treating non-small-cell lung cancer (NSCLC) with EGFR mutations. Genetic testing is required to detect the mutation for selecting patients who can use osimertinib. Here, we report an attempt to develop nuclear imaging probes that detect the EGFR mutations. We designed and synthesized I-osimertinib and Br-osimertinib with a radioactive or nonradioactive halogen atom at an indole ring in osimertinib and evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…1,2 When activated by ligands such as the epidermal growth factor (EGF), the receptor undergoes dimerization, leading to autophosphorylation of its cell domain and subsequent activation of downstream pathways. [3][4][5] Over-expression and abnormal activation of EGFR protein are closely related to the development and metastasis of various cancers, including non-small cell lung cancer (NSCLC), ovarian cancer, pancreatic cancer, and breast cancer, among others. [6][7][8] Consequently, EGFR serves not only as a biomarker with clinical value but also as a target for related cancer diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 When activated by ligands such as the epidermal growth factor (EGF), the receptor undergoes dimerization, leading to autophosphorylation of its cell domain and subsequent activation of downstream pathways. [3][4][5] Over-expression and abnormal activation of EGFR protein are closely related to the development and metastasis of various cancers, including non-small cell lung cancer (NSCLC), ovarian cancer, pancreatic cancer, and breast cancer, among others. [6][7][8] Consequently, EGFR serves not only as a biomarker with clinical value but also as a target for related cancer diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…On the other aspect, indole compounds possess impressive antihistaminic, [17] antifungal, [18] antimicrobial, [19] antiallergy, [20] anti-HIV [21] and anticancer pharmaceutical activities. [22] Owing to the biologically important properties of both organotellurides and indole compounds, it should be highly desirable to synthesize the tellurolated indoles, a class of compounds that have not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For examples, studies have shown that phenyl−tellurocysteine ( I ) was a stronger inhibitor of several human cytochrome P450 isoenzymes compared with phenylselenocysteine and phenylthiocysteine, [11f] 2‐phenyl tellurenyl‐1‐naphthol ( II ) has a significant effect on inhibiting stimulating LTB4 biosynthesis in human neutrophils, [14] water‐soluble 8‐(phenyltellanyl)octyl sulfate sodium ( III ) can efficiently protect against peroxynitrile‐induced oxidation, [15] diaryl telluride ( IV ) at low concentration can present a protective effect on DNA damage without modifying the hemolysis rate, [16] δ‐tocopherol analogue ( V) is an important antioxidant and organotelluride VI is a potent inhibitor of thioredoxin reductase with IC 50 values between 2 and 4 μ M [14,15] (Figure 1). On the other aspect, indole compounds possess impressive antihistaminic, [17] antifungal, [18] antimicrobial, [19] antiallergy, [20] anti‐HIV [21] and anticancer pharmaceutical activities [22] . Owing to the biologically important properties of both organotellurides and indole compounds, it should be highly desirable to synthesize the tellurolated indoles, a class of compounds that have not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the fact that we aimed to develop radioiodine-labeled probes, based on the availability of the starting materials and the similarity between iodine and bromine, 25,26 we first generated vesamicol derivatives comprising the bromine atom ( 3–14 ); indeed, we synthesized compounds by coupling trans -2-(1-piperazinyl)cyclohexanol or trans -2-(1-piperazinyl)cyclopentanol ( 20 , Scheme 1) with bromophenylalkyl bromide or bromophenylalkyl methanesulfonate (Scheme 2). 33,34…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the fact that we aimed to develop radioiodine-labeled probes, based on the availability of the starting materials and the similarity between iodine and bromine, 25,26 we first generated vesamicol derivatives comprising the bromine atom (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14); indeed, we synthesized compounds by coupling trans-2-(1-piperazinyl)cyclohexanol or trans-2-(1-piperazinyl)cyclopentanol (20, Scheme 1) with bromophenylalkyl bromide or bromophenylalkyl methanesulfonate (Scheme 2). 33,34 The binding affinities of 3-14 for the sigma receptors (sigma-1 and sigma-2) were determined by conducting competitive binding assays. Among them, one derivative (11) exhibited high selectivity for the sigma-1 receptor and another (12) exhibited high affinity for both the sigma-1 and sigma-2 receptors.…”
Section: Introductionmentioning
confidence: 99%